2013
DOI: 10.1371/journal.pgen.1003885
|View full text |Cite
|
Sign up to set email alerts
|

PNUTS/PP1 Regulates RNAPII-Mediated Gene Expression and Is Necessary for Developmental Growth

Abstract: In multicellular organisms, tight regulation of gene expression ensures appropriate tissue and organismal growth throughout development. Reversible phosphorylation of the RNA Polymerase II (RNAPII) C-terminal domain (CTD) is critical for the regulation of gene expression states, but how phosphorylation is actively modified in a developmental context remains poorly understood. Protein phosphatase 1 (PP1) is one of several enzymes that has been reported to dephosphorylate the RNAPII CTD. However, PP1's contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 76 publications
3
81
0
Order By: Relevance
“…shown to associate with RNA polymerase II (RNAPII) at active sites of transcription and enhance the dephosphorylation of the RNAPII C-terminal domain (CTD) residue Ser5 (20,21). Remarkably, despite its role in these processes, the molecular function of PNUTS is still largely uncharacterized.…”
mentioning
confidence: 99%
“…shown to associate with RNA polymerase II (RNAPII) at active sites of transcription and enhance the dephosphorylation of the RNAPII C-terminal domain (CTD) residue Ser5 (20,21). Remarkably, despite its role in these processes, the molecular function of PNUTS is still largely uncharacterized.…”
mentioning
confidence: 99%
“…2A, Table 1) in nuclear extracts and is also able to dephosphorylate the C-terminal domain of this polymerase, at least in vitro [34,47]. Recently it was shown that PNUTS:PP1 complex enhances the dephosphorylation of RNAPII C-terminal domain (CTD) residue Ser5 [48,49].…”
Section: Gene Transcription and Rna Processingmentioning
confidence: 99%
“…BCAR4 is required for the transcriptional activation of phospho-GLI2-dependent target genes in breast cancer cells. In response to CCL21, BCAR4 binds to Smad Nuclear Interacting Protein 1 (SNIP1) (109) and serine/threonine phosphatase regulatory subunit 10 (PSP1R10) also known as PNUTS (110). Interaction of phospho-GLI2 with SNIP1 releases SNIP1-mediated inhibition of p300-dependent histone acetylation, which results in binding of PNUTS to H3K18ac, thereby releasing inhibition of pol II via activation of phosphatase PP1 ( Figure 1F) (111).…”
Section: Lncrna Bcar4 (Breast Cancer Anti-estrogen Resistance)mentioning
confidence: 99%